Metabolic Effects of Loquat Juice (Eriobotrya japonica Lindl Mkarkeb Variety) on Lipid Homeostasis, Liver Steatosis, and Oxidative Stress in Hyperlipidemic Mice Fed a High-Fat–High-Fructose Diet - Imane Mokhtari; Thamer Aljutaily; Huda Aljumayi; Khadija S. Radhi; Abdulkarim S. Almutairi; Hassan Barakat; Ibrahim Khalifa; Souliman Amrani; Hicham Harnafi (Metabolites)
Background: Loquat fruit is consumed for its flavorful taste and a rich array of health-promoting compounds like phenolics, flavonoids, and carotenoids. This study aimed at the biochemical characterization of fresh juice from the Moroccan Mkarkeb variety of loquat and evaluating its effects on lipid homeostasis and liver steatosis in hyperlipidemic mice. Methods: The biochemical characterization followed AOAC methods. In vivo study involved hyperlipidemic mice fed a high-fat, high-fructose diet for 6 weeks and treated with loquat juice at 3.5 and 7 mL kg−1 or fenofibrate at 4 mg·kg−1. The concentrations of lipids in plasma, liver, adipose tissue, feces, and bile and blood glucose levels were quantified. Liver steatosis was visually examined and confirmed histologically, and liver injury markers (AST, ALT, ALP, LDH, and TB) were measured. Liver oxidative stress was assessed by measuring MDA content and antioxidative enzyme activities. Results: Our findings indicate that fresh loquat juice is poor in fat and protein and contains moderate sugars with a low energy value (40.82 ± 0.25 kcal/100 g). It is also rich in minerals, vitamin C, phenolic acids, flavonoids, and carotenoids. The juice effectively restored lipid metabolism by enhancing reverse cholesterol transport and lowering LDL-cholesterol, triglycerides, and the atherogenic index. The studied juice decreases blood glucose and prevents weight gain and lipid accumulation in the liver and adipose tissue. The juice prevents lipotoxicity-induced liver injury, corrects toxicity markers, and improves the liver’s morphological and histological structures. It also reduces oxidative stress by lowering MDA and activating SOD and catalase. Conclusions: The juice holds high nutritional and medicinal value, potentially preventing lipid disorders and cardiovascular issues.